A dynamic programming model for hospitality performance in tourist cities - Sheng, Li (Publishing House of Wroclaw University of Economics and Business, 2024)
The paper suggests the use of a dynamic programming model to describe how external shocks from tourism source markets are dispersed across visitor flows to a travel destination, with major effects on the destination’s hospitality performance. One can determine the driving forces underlying local cycles by modelling this mechanism, which also provides a theoretical foundation for empirical research. Additionally, the study revealed that in an equilibrium tourism market, positive changes in the push and pull variables have a beneficial influence on the local economy, resulting in decreased prices and increases in the number of visitors and revenues. In contrast, a negative external shock can have a detrimental influence on these aspects of the local economy.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 144-158
Keywords: dynamic programming; propagation mechanism; hospitality fluctuation; tourism flows; travel destinations